2018
DOI: 10.1142/s0219649218500430
|View full text |Cite
|
Sign up to set email alerts
|

A New Associative Classification Algorithm for Predicting Groundwater Locations

Abstract: In this paper, we study the problem of predicting new locations of groundwater in Jordan through the application of a proposed new method, Groundwater Prediction using Associative Classification (GwPAC). We identify features that differentiate locations of groundwater wells according to whether or not they contain water. In addition, we survey intelligent-based methods related to groundwater exploration and management. Three experimental analyses were conducted with the objective to evaluate the capability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Approximately 60% of the references collected contribute to seven out of nine goals related to water supply; goal 2.a., which focuses on developing a secure and safe water supply in the area, is included in six studies; four focus on allocating new water sources [56][57][58][59], and two studies focus on sustainable management [52,60]. While six studies were found to be aligned with goal 2.b., which focuses on using desalinated water as a major source for water supply, four focused on saline water intrusion [43,[61][62][63], one on hydrochemistry [42], and one on salinization scenarios [64].…”
Section: Goals Related To Water Supplymentioning
confidence: 99%
See 1 more Smart Citation
“…Approximately 60% of the references collected contribute to seven out of nine goals related to water supply; goal 2.a., which focuses on developing a secure and safe water supply in the area, is included in six studies; four focus on allocating new water sources [56][57][58][59], and two studies focus on sustainable management [52,60]. While six studies were found to be aligned with goal 2.b., which focuses on using desalinated water as a major source for water supply, four focused on saline water intrusion [43,[61][62][63], one on hydrochemistry [42], and one on salinization scenarios [64].…”
Section: Goals Related To Water Supplymentioning
confidence: 99%
“…About 35% of the collected documents focused on modeling in terms of: (a) estimating the recharge rate [50,106], (b) enhancing the recharge amount [78,80,81,84,85,[87][88][89][90]92], (c) studying the impact of climate change on water resources [53], (d) assessing surface water and drought [51,55,107], (e) locating potential areas for groundwater abstraction [58,59], (f) analyzing time series [32,108], (g) building water quality models [70], (h) building groundwater models [29][30][31]54,[96][97][98], (i) delineating isohyetal maps for rainfall [93], (j) creating vulnerability maps [65][66][67], and (k) proposing sustainable water management plans [52,60].…”
Section: Research Focus Areas Analysismentioning
confidence: 99%
“… Aburub & Hadi (2018) developed an associative classification algorithm for prediction of existence of underground water at a given place. Again this algorithm has been developed for associative classification of fully-labeled data.…”
Section: Related Workmentioning
confidence: 99%
“…The frequency of patterns is also called the support and the associativity of a pattern is called the confidence . The difference between associative classification and ARM is that in an associative classification rule consequent is always a class label ( Aburub & Hadi, 2018 ). Associative classification has shown better performance than non-associative classifiers ( Shahzad & Baig, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…PBC4cip has been shown to outperform at least eight state-of-the-art algorithms designed for class imbalance problems [26,30].…”
mentioning
confidence: 99%